Urgensi Administrasi Pendidikan dalam Meningkatkan Mutu Pendidikan di Indonesia: dalam Perspektif Islam - Della Sapitri; Maya Sari Nasution; Ahmad Sabri; Rully Hidayatullah (Pusat Riset dan Inovasi Nasional, 2025)
This research discusses the urgency of educational administration in improving the quality of education in Indonesia from an Islamic perspective. This research aims to analyze how the application of educational administration principles based on Islamic values can contribute to the achievement of national education goals. Through a literature study approach, this research identifies various challenges faced, such as the quality of educators and limited facilities and infrastructure. Research results show that effective and efficient educational administration, which integrates values such as honesty, justice, and responsibility, can enhance the overall quality of education. This finding is expected to contribute to the development of a more relevant and effective educational administration model in Indonesia, as well as encourage policymakers to apply these principles in everyday educational practices.